1985
DOI: 10.1149/1.2113832
|View full text |Cite
|
Sign up to set email alerts
|

ESCA and Photoelectrochemical Studies of p‐n Junction Silicon Electrodes Protected by Platinum Deposition for Use in Solar Energy Conversion

Abstract: Layers of mixed platinum and silicon were formed on p~-n junction silicon single crystal wafers (hereafter abbreviated as p~n-Si) by depositing Pt on the p~-Si surface, followed by heating at 320~176 ESCA studies showed that Pt silicide (PtSi, or in some cases a mixture of PtSi and Pt2Si) was formed when a 3-5 nm-thick Pt layer on Si was heated, whereas a nonstoichiometric, St-rich Pt-Si intermixed layer was formed when an ultrathin Pt layer (1.0 nm thick) on Si was heated. It was also confirmed that, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…On the bare PS photoelectrode, a large overpotential is observed and the onset potential (E OS ) is measured to be −0.1 V. On the other hand, when the PS photocathode is impregnated with Pt electrocatalyst by the electroless deposition, the overpotential is dramatically reduced and the E OS value is enhanced to +0.1 V. Note the electrode potential (E) is against the reversible hydrogen electrode (RHE) and a positive photovoltage indicates a positive energy conversion of photon to H 2 . The enhancement of H 2 generation characteristics in the presence of Pt electrocatalyst is similar to the case of planar Si photocathode 12,17,18 and can be contributed to more facile H + reduction on Pt electrocatalyst than on bare PS surface. As E is scanned in negative direction, a current plateau is observed.…”
Section: Resultssupporting
confidence: 52%
“…On the bare PS photoelectrode, a large overpotential is observed and the onset potential (E OS ) is measured to be −0.1 V. On the other hand, when the PS photocathode is impregnated with Pt electrocatalyst by the electroless deposition, the overpotential is dramatically reduced and the E OS value is enhanced to +0.1 V. Note the electrode potential (E) is against the reversible hydrogen electrode (RHE) and a positive photovoltage indicates a positive energy conversion of photon to H 2 . The enhancement of H 2 generation characteristics in the presence of Pt electrocatalyst is similar to the case of planar Si photocathode 12,17,18 and can be contributed to more facile H + reduction on Pt electrocatalyst than on bare PS surface. As E is scanned in negative direction, a current plateau is observed.…”
Section: Resultssupporting
confidence: 52%
“…Several investigators have attempted to protect photoelectrodes using coatings of electrocatalytically active metal thin lms, covalent electroactive molecular species, dark photoactive conducting polymers such as polypyrrole, polyaniline, polyacetylene, etc., or by use of less corrosive non-aqueous electrolytes. [24][25][26][27][28][29][30][31][32][33][34] To date these efforts have not been wholly satisfactory. With coatings of electroactive metal thin lms such as platinum, iridium, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, a long-term challenge in assembling high-performance, stable PECs with semiconductor wafers is to prevent the semiconductors from corrosion caused by the holes generated in the photon-induced charge separation processes . In the last several decades, a lot of experimental and theoretical effort has indicated that depositing a submonolayer of well-separated nanoclusters made of noble metals on the surface of a semiconductor wafer could significantly increase the stability of the PEC fabricated with the metal/semiconductor hybrid photoelectrode. , The metal nanoclusters play a role in modulating the distribution of Schottky barriers over the semiconductor/electrolyte interface and directing the holes to flow into the electrolyte through the metal nanoclusters. , The elimination of charge flow through the semiconductor/electrolyte interface inhibits corrosion of the semiconductor. The ideal morphology of each metal nanocluster is a “mushroom” shape, which has a very thin root with a diameter of less than 10 nm bonding to the semiconductor substrate and a large cap with suitable geometry and size for exposing the semiconductor surface as much as possible in order to harvest sunlight …”
Section: Introductionmentioning
confidence: 99%